Plant Proton Pumps and Cytosolic pH-Homeostasis - Cosse, Maike; Seidel, Thorsten (Frontiers in Plant Science, 2021)
Proton pumps create a proton motif force and thus, energize secondary active transport at the plasma membrane and endomembranes of the secretory pathway. In the plant cell, the dominant proton pumps are the plasma membrane ATPase, the vacuolar pyrophosphatase and the vacuolar-type ATPase. All these pumps act on the cytosolic pH by pumping protons into the lumen of compartments or into the apoplast. To maintain the typical pH and thus, the functionality of the cytosol, the activity of the pumps needs to be coordinated and adjusted to the actual needs. The cellular toolbox for a coordinated regulation comprises 14-3-3 proteins, phosphorylation events, ion concentrations and redox-conditions. This review combines the knowledge on regulation of the different proton pumps and highlights possible coordination mechanisms.